Physical quantity of residue electrostatic energy in flavin mononucleotide binding protein dimer. (February 2018) - Nunthaboot, Nadtanet; Nueangaudom, Arthit; Lugsanangarm, Kiattisak; Pianwanit, Somsak; Kokpol, Sirirat; Tanaka, Fumio
Graphical abstract: Highlights: The Electrostatic (ES) energy of each residue was first time quantitatively evaluated in flavin mononucleotide binding protein (FBP). Among all residues, both Arg63 and Glu13 mainly contribute to Sub A–Sub B binding. The FMN molecule greatly stabilizes the protein structure within a subunit. The present work reveals that the ES energy not only plays an important role on ET phenomena but also in the protein stabilization in general. Abstract: The electrostatic (ES) energy of each residue was for the first time quantitatively evaluated in a flavin mononucleotide binding protein (FBP). A residue electrostatic energy (RES) was obtained as the sum of the ES energies between atoms in each residue and all other atoms in the FBP dimer using atomic coordinates obtained by a molecular dynamics (MD) simulation. ES is one of the most important energies among the interaction energies in a protein. It is determined from the RES, the residues which mainly contribute to stabilize the structure of each subunit, and the binding energy between two subunits can be estimated. The RES of all residues in subunit A (Sub A) and subunit B (Sub B) were attractive forces, even though the residues contain net negative or positive charges. This reveals that the ES energies of any of the residues can contribute to stabilize the protein structure. The total binding ES energy over all residues among the subunits was distributed between −0.2 to −1.2 eV (mean = −0.67 eV) from the MD simulation time.